2022
DOI: 10.1039/d2gc02860c
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of PET glycolysis by applying recyclable heterogeneous organocatalysts

Abstract: Chemical depolymerisation, or solvolysis, can be a sustainable plastic recycling method, as a circular economy can be achieved by recovering the pure monomers. Polyethylene terephthalate (PET) is a ubiquitous plastic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 52 publications
(78 reference statements)
0
24
0
Order By: Relevance
“…The glycolysis of post-consumer PET waste is carried out in the presence of a transesterification catalyst. In the literature, various catalysts have been reported that include metal acetates (cobalt, lead, zinc, and manganese), [18][19][20] less efficient sodium carbonate and sodium bicarbonate, 21 titanium phosphate, 22 deep eutectic solvents, 23 organic catalysts, 24 heterogeneous catalysts, [25][26][27][28] and ionic liquids of zinc and copper acetate. 29 The most active glycolysis catalyst is zinc acetate, but as a heavy metal, zinc is toxic to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…The glycolysis of post-consumer PET waste is carried out in the presence of a transesterification catalyst. In the literature, various catalysts have been reported that include metal acetates (cobalt, lead, zinc, and manganese), [18][19][20] less efficient sodium carbonate and sodium bicarbonate, 21 titanium phosphate, 22 deep eutectic solvents, 23 organic catalysts, 24 heterogeneous catalysts, [25][26][27][28] and ionic liquids of zinc and copper acetate. 29 The most active glycolysis catalyst is zinc acetate, but as a heavy metal, zinc is toxic to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative catalysts include nanoparticles, ionic liquids, light metal salts, zeolites, organocatalysts, and deep-eutectic solvents. [13][14][15][24][25][26] Most recently, the use of protic ionic salts as catalysts in the depolymerization of PET has removed the metal component of the catalyst, resulting in products that are more benign. 20,27 Blending polymers together provides an additional pathway to use polymers at their end of life.…”
Section: Introductionmentioning
confidence: 99%
“…Besides homogeneous metal salt-based catalysts, now heterogeneous catalysts are also widely used for PET glycolysis. Fehér et al demonstrated that organocatalyst-modified silica gels are efficient for PET glycolysis achieving a non-isolated BHET yield of 88.5% under optimum conditions (190 °C, 1.7 h,) by handling only 384 mg of PET substrate in a reaction vial [ 15 ]. Recently Kim et al reported the glycolysis of PET waste into BHET using oyster shell-derived catalysts with a BHET yield of 68.6% at 195 °C [ 16 ].…”
Section: Introductionmentioning
confidence: 99%